Exciton polariton condensate transistors - Ng, Jing Yang (Nanyang Technological University, 2023)
In this report, I studied the behaviour of exciton polariton condensate system in the context of microcavity nodes and proposed methods to exploit its properties for making perceptron. I first found the analytical equilibrium solutions to a three nodes toy model of perceptron in the weak coupling limit and demonstrated the bistable nature of the exciton polariton condensate system along with an unstable equilibrium. Then, I characterized the different regimes in the parameter space where bistability manifests and found the conditions that will guarantee the transition between these two stable states. This allows the exciton polariton systems to carry binary information which is an essential property for developing an information processing architecture using these systems. I also analysed some limitations of the system, namely the incompatibility of having the system to be scalable and unidirectional at the same time. This led me to consider introducing a non-Hermitian hopping parameter between the nodes which makes perfect unidirectionality possible. This allows a system of nodes to be partially decoupled such that each node only depends on its inputs and not on its output, greatly simplifying the dynamic of the system. Finally, with an additional assumption that there exists some phase alignment mechanism, I proposed how the full set of logic gates can be realizable by using the microcavity exciton polariton system.